BURNOUT LEVELS IN ONLINE LEARNING AT NEW NORMAL ERA OF COVID-19 PANDEMI USING ARCHERY AS PLAYING CONCEPT ON SMP-IT IBNU SINA WULUHAN STUDENTS - Akhmad, Efrizal Amrullah; Warsito, Sugiono; Farda M, Luthfi (International Islamic Medicine Forum, 2022)
The Covid-19 pandemic requires SMP-IT Ibnu Sina Wuluhan students to carry out online learning at home to reduce transmission of the virus. Many problems occure from the policy such as: tasks that must be completed in a short time, rigid study hours, limited quotas and gadgets and signal constraints that cause burnout in students. One way to overcome this problem is doing archery as playing concept. The purpose of this study was to determine the effect of archery on reducing burnout levels. The research took place at SMP-IT Ibnu Sina Wuluhan using a quasi-experimental one group pretest-posttest design method and was held in February-July 2021. 64 respondents used as total sample. The results showed a decrease in the level of burnout after doing archery. The analysis test using the Wilcoxon Signed-Rank and shows the Asymp. Sig value. (2-tailed) 0.000 at alpha value (α) < 0.05 so Ho is rejected. Thus, there is an effect of playing archery on reducing the level of burnout. Burnout is a serious problem in online learning so it requires proper handling because it has an impact on learning and student achievement. The learning process must be carried out calmly and comfortably so that it can improve the quality of students. Archery, which is packaged with the concept of playing, can be one way to reduce burnout levels during online learning. This archery sport focuses as a means of entertainment that can provide a sense of pleasure and comfort.